The Role of the Didactic Games in Enhancing Cognitive Activity at Preschool Children - Gasim qızı, Aliyeva Shahla (2020)
The Article is dedicated to learn the impact of increasing cognitive activity in preschool children. 44 children aged 5-6 were selected for the research and the impact on the cognitive activity through didactic games with them were investigated. Different aspects manifested itself in development of cognitive processes, especially mentality during the comparison of methodologies used in conducting didactic games with children on the experimental and control groups in the research process. Unlike the control groups, the experimental groups were more likely to observe cognitive processes and tasks, and the tasks were performed more adequate by the experimental group. It is determined that organization of transforming didactic games into a leading activity in preschool preparation of children and trying to improve the activity of game increases the cognitive activity. The research has shown that there is a significant dependence between increasing the cognitive activity and didactic games.